Decoding oral cancer: insights from miRNA expression profiles and their regulatory targets - Wang, Xin; Zhang, Shuang; Wang, Shuyi; Cao, Tao; Fan, Hong (Frontiers in Molecular Biosciences, 2025)
Oral cancer (OC) is a prevalent malignancy with high mortality rates, largely attributed to late diagnosis and limited therapeutic advancements. MicroRNAs (miRNAs), as critical regulators of gene expression, have emerged as key players in modulating plethora of cellular mechanisms. This study analyzed miRNA and gene expression profiles in OC using publicly available datasets from the Gene Expression Omnibus (GEO) to explore their roles in tumorigenesis. A total of 23 differentially expressed miRNAs (DEmiRs) and 1,233 differentially expressed genes (DEGs) were identified. Functional annotation and pathway enrichment analyses highlighted significant involvement of DEmiRs and their target genes in cell cycle-related processes, including enrichment in the nucleus, transcription factor activity, regulation of nucleosides, nucleotide and nucleic acids, cell growth and/or maintenance, mitotic cell cycle, mitotic M-M/G1 phases an DNA replication. Furthermore, different signaling cascades such as IGF signaling, PDGF signaling and LKB1 signaling and PLK1 signaling pathways were also found associated with DEmiR-related regulation of OC progression. Protein-protein interaction (PPI) network analysis identified key molecular hubs associated with DEmiR and DEGs in OC. Notably, most of these hub genes such as NEK2, NDC80, NUF2, PLK1, SMAD2, TP53, TPX2, TTK, UBE2C, WDHD1, WTAP, YWHAZ are directly or indirectly associated with cell cycle progression, underscoring the role of DEmiRs in driving tumor proliferation and survival in OC via dysregulating cell cycle. This study offers insights into the molecular mechanisms underlying OC and highlights miRNAs as potential biomarkers and therapeutic targets to disrupt the cancerous cell cycle and improve treatment outcomes.